GyPSuM: A joint tomographic model of mantle density and seismic wave speeds - Simmons, Nathan A.; Forte, Alessandro M.; Boschi, Lapo; Grand, Stephen P. (Journal of Geophysical Research: Solid Earth, 2010)
GyPSuM is a 3‐D model of mantle shear wave (S) speeds, compressional wave (P) speeds, and density. The model is developed through simultaneous inversion of seismic body wave travel times (P and S) and geodynamic observations while using realistic mineral physics parameters linking wave speeds and density. Geodynamic observations include the global free air gravity field, divergence of the tectonic plates, dynamic topography of the free surface, and the flow‐induced excess ellipticity of the core‐mantle boundary. GyPSuM is built with the philosophy that heterogeneity that most closely resembles thermal variations is the simplest possible solution. Models of the density field from Earth's free oscillations have provided great insight into the density configuration of the mantle but are limited to very long wavelength solutions. Alternatively, scaling higher‐resolution seismic images to obtain density anomalies generates density fields that do not satisfy geodynamic observations. The current study provides a 3‐D density model for the mantle that directly satisfies geodynamic and seismic observations through a joint seismic‐geodynamic inversion process. Notable density field observations include high‐density piles at the base of superplume structures, supporting the general results of past normal mode studies. However, we find that these features are more localized and have lower amplitude than past studies would suggest. When we consider both fast and slow seismic anomalies in GyPSuM, we find that P and S wave speeds are strongly correlated throughout the mantle. However, we find a low correlation of fast S wave zones in the deep mantle (>1500 km depth) with the corresponding P wave anomalies, suggesting a systematic divergence from simplified thermal effects in ancient subducted slab anomalies. The cratonic lithosphere and D″ regions are shown to have strong compositional signatures. However, we argue that temperature variations are the primary cause of P wave speed, S wave speed, and density anomalies throughout most of the mantle.